2000
DOI: 10.1152/ajpcell.2000.279.6.c1812
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-induced translocation of protein kinase C isoforms visualized in renal epithelial cells

Abstract: Short-term regulation of sodium metabolism is dependent on the modulation of the activity of sodium transporters by first and second messengers. In understanding diseases associated with sodium retention, it is necessary to identify the coupling between these messengers. We have examined whether dopamine, an important first messenger in tubular cells, activates and translocates various protein kinase C (PKC) isoforms. We used a proximal tubular-like cell line, LLCPK-1 cells, in which dopamine was found to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 22 publications
6
35
0
1
Order By: Relevance
“…Based on these data that show dramatic changes in actin at the apical membrane within 20 min, we postulate that the time taken to reach maximum albumin uptake is required for the de novo assembly of the actin substructure and the recruitment of the proteins required to form the endocytic complex. A similar rapid time frame has been shown for the translocation of PKC-␣ in LLC-PK 1 cells treated with dopamine (30). Treatment of OK cells with dopamine, which increases cAMP levels, leads to a rapid downregulation of NHE3 activity resulting from increased clathrinmediated endocytosis of NHE3 protein (3,17).…”
Section: Discussionsupporting
confidence: 66%
“…Based on these data that show dramatic changes in actin at the apical membrane within 20 min, we postulate that the time taken to reach maximum albumin uptake is required for the de novo assembly of the actin substructure and the recruitment of the proteins required to form the endocytic complex. A similar rapid time frame has been shown for the translocation of PKC-␣ in LLC-PK 1 cells treated with dopamine (30). Treatment of OK cells with dopamine, which increases cAMP levels, leads to a rapid downregulation of NHE3 activity resulting from increased clathrinmediated endocytosis of NHE3 protein (3,17).…”
Section: Discussionsupporting
confidence: 66%
“…One can hypothesize that the observed reduction of cytosolic Ca 2ϩ concentrations upon glucose stimulation might result in lower ATP consumption by reticulum ATP-dependent Ca 2ϩ pumps. In addition, hyperpolarizing effects of dopamine in beta cells could diminish the activation of the sodium/ potassium ATP pump, as demonstrated in renal cells (29). All these results indicate that the increase in glucose-induced ATP generation induced by dopamine could be the consequence of reduced ATP consumption.…”
Section: Discussionmentioning
confidence: 70%
“…DA translocates the enzyme so that it acts as a integral membrane protein and this, in turn, can activate pumps and/or transporting channels, as demonstrated in an experiment in proximal tubule cells. 37 In this experiment, Nowicki and Cols demonstrated that dopamine interacts with PKC, in Ca + -dependent and independent mechanisms. PKC stimulation by DA would be induced by D 1A receptors that would increase cAMP levels, thus activating PKA which, in turn, would further activate PKC.…”
Section: Pkc (Protein Kinase C)mentioning
confidence: 83%